2016
DOI: 10.7314/apjcp.2016.17.3.1111
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Health Educational Program Based on Self-Efficacy and Social Support for Preventing Liver Fluke Infection in Rural People of Surin Province, Thailand

Abstract: Opisthorchiasis is a major problem in Thailand particularly in northeast region which also has a high incidence of cholangiocarcinomas. Since health modification is needed, this quasi-experimental study aimed to assess the effectiveness of a health education program based on self-efficacy and social support in Tha Tum district, Surin province, Thailand. A total of 70 participants were purposive selected with a history of opisthorchiasis. Participants were divided into experimental and control groups, each with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The health promotion campaign provided through the VHV scheme was effective inasmuch as there were individuals who adhere to the messaging. Among the strengths of the VHV scheme that several studies (Kaewpitoon et al, 2016; Lyttleton, 1996; WHO, 2007) assessed was the capability of health volunteers to formulate their messages to reflect the local community’s lifestyle. Whether the aim was for infectious or non-communicable diseases, the health volunteers were able to provide clear communication.…”
Section: Discussionmentioning
confidence: 99%
“…The health promotion campaign provided through the VHV scheme was effective inasmuch as there were individuals who adhere to the messaging. Among the strengths of the VHV scheme that several studies (Kaewpitoon et al, 2016; Lyttleton, 1996; WHO, 2007) assessed was the capability of health volunteers to formulate their messages to reflect the local community’s lifestyle. Whether the aim was for infectious or non-communicable diseases, the health volunteers were able to provide clear communication.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is necessary to find out a suitable model or method for reducing the risk factors, such as using the model of having village health volunteers in high-risk areas in Thailand with a shortage of health personnel [ 19 ] or the parallel program of village health volunteers in the twin cities (Thailand–Laos) [ 18 ] to prevent and reduce CCA risk factors. In addition, some high-risk areas have adopted a public health approach [ 20 – 23 ] or one health approach [ 24 , 25 ] to reduce risk factors or control OV and CCA.…”
Section: Discussionmentioning
confidence: 99%
“…No OVinfected Bithynia snails, the first intermediate host, were detected in the lake after six years of implementation [28]. Several studies in Thailand have also indicated a correlation between the self-efficacy application on the health education programme for preventing OV and CCA [12][13][14][15]. There is some critical evidence that public health programmes are beneficial: without behavioural modifying public health processes, 86% of the infection could relapse [29].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have presented models for behaviour modification and reducing CCA risk in northeast Thailand. Health education programmes for preventing OV and CCA by applying the self‐efficacy concept of Bandura [11] were designed in the Nakhon Ratchasima [12, 13], the Surin [14] and the Khon Kaen [15]. Moreover, a group process study was applied to change consumption behaviour causing OV infection risk in the Sakon Nakhon [16].…”
Section: Introductionmentioning
confidence: 99%